The impact of the COVID-19 pandemic on time to treatment in head and neck cancer management: a systematic review - Malte Grumstrup Simonsen; Amanda-Louise Fenger Carlander; Kathrine Kronberg Jakobsen; Christian Grønhøj; Christian von Buchwald (Acta Oncologica)
Background and purpose: Coronavirus disease 2019 (COVID-19) caused a need for reorganization in the healthcare systems. First, we aimed to determine the impact of the COVID-19 pandemic on time to treatment in head and neck cancer (HNC) patients. Second, we aimed to determine the impact of COVID-19 on tumor stage and changes in treatment regimens used.